Comparative Evaluation of Antimicrobial Efficacy of Aloe Barbadensis Miller, Curcuma Longa and Azadirachta Indica with Sodium Hypochlorite: An Invitro Study - James, Dr. Vandana; Balagopal, Dr.Sundaresan.; Charanya, Dr.C.; .L, Marshal; S, Nandhini. (Journal of Biomedical and Pharmaceutical Research, 2023)
Context: The thorough removal of microflora, debris, and irritants from the root canal system is necessary for root canal treatment to be effective. Herbal or natural products are becoming more popular recently as a result of their strong antibacterial activity, biocompatibility, anti-inflammatory, and anti-oxidant propertiesAims: To compare and evaluate antimicrobial efficacy of herbal extracts Aloe barbadensis miller, Curcuma longa and Azadirachta indica with 2.5% sodium hypochlorite against the Enterococcus faecalis .Settings and Design: Forty muller Hinton agar plates were taken as sample and were grouped into 4 groups as Group I: 2.5% NaOCl ,Group II: Curcuma longa extract ,Group III: Azadirachta indica extract, Group IV: Aloe barbadensis miller.Methods and Material: The agar plates were inoculated with strains of E.faecalis (ATCC29212) and test solutions were placed in agar wells in group 1-4. The agar plates were incubated at 37 0C for 72 hours. After incubating, the agar plates were examined for zone of inhibition for assessing the degree of susceptible or resistance of test organism.Statistical analysis used: Statistical analysis was performed using Oneway Anova test with statistical significance at P < 0.05.Results: It was shown that Curcuma longa was highly efficient similar to 2.5%NaOClConclusions: Curcuma longa extract has a significant antimicrobial efficacy against Enterococcus faecalis similar to 2.5% sodium hypochloriteKey Messages: Herbal irrigants are best alternative to gold standard chemical endodontic irrigants. With their increase in antimicrobial properties, they aid in complete removal of endodontic microorganisms.